Quasar – CIV forest cross-correlation with SDSS DR12. Issue 1 (7th July 2018) - Gontcho A Gontcho, Satya; Miralda-Escudé, Jordi; Font-Ribera, Andreu; Blomqvist, Michael; Busca, Nicolás G; Rich, James
ABSTRACT: We present a new determination of the large-scale clustering of the CIV forest (i.e. the absorption due to all CIV absorbers) using its cross-correlation with quasars in the Sloan Digital Sky Survey Data Release 12. We fit a linear bias model to the measured cross-correlation. We find that the transmission bias of the CIV forest, bFc, at a mean redshift of $z\, =\, 2.3$, obeys $(1\, +\, β _c)b_{F c}=-0.024\, ± \, 0.003$ . Here, β c is the linear redshift space distortion parameter of the CIV absorption, which can only be poorly determined at β c = 1.1 ± 0.6 from our data. The most accurately determined combination marginalized over β c is $(1\, +\, 0.44\, β _c)b_{F c}=-0.0170\, ± \, 0.0014$ . The transmission bias is related to the bias of CIV absorbers and their host haloes, b τ c, through the effective mean optical depth of the CIV forest, which we estimate at $\bar{τ }_c(z) \simeq 0.01$ from previous studies of the CIV equivalent width distribution. We then find 1 < b τ c < 1.7, with the large error arising from uncertainties in β c and $\bar{τ }_c$ . This CIV bias is lower than the DLA bias b DLA ≃ 2 measured previously from the cross-correlation of DLAs and the Ly α forest, indicating that most CIV absorbers are hosted by haloes of lower mass than DLAs. More accurate determinations of $\bar{τ }_c(z)$ and β c are necessary to check this conclusion.